Improving Engineering Students' Learning Outcomes in Electrical Engineering Materials with ModelTeam Assisted Individualization - Setiawan, Doni; Faoziyah, Nina (JUPE : Jurnal Pendidikan Mandala, 2025)
Low student learning outcomes were a problem in this classroom action research. This was evident in the students' lack of understanding of the material, their rapid boredom, and their lack of active participation in learning activities due to the lack of diverse learning methods. The purpose of this research was to improve student learning outcomes through learning models. Team Assisted Individualization on dynamic electricity material. This type of research is classroom action research conducted over two cycles on 12 second-semester students of the D3 Electrical Engineering study program at Muhammadiyah University of Tegal. Observations and written tests are the data obtained in this study. Data analysis is calculated based on a percentage scale and a predetermined table of conceptual understanding interpretations. The results of this study prove that the use of the model Team Assisted Individualization can improve student learning outcomes since cycle I with a percentage of 67% in the good category, then in cycle II it became 92% in the very good category. So, it can be concluded that with the learning model Team Assisted Individualization, Student learning outcomes on the Dynamic Electricity material can be increased.